2021
DOI: 10.1002/smll.202103798
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strain in N‐Doped Palladium/Amorphous‐Cobalt (II) Interface Facilitates Alkaline Hydrogen Evolution

Abstract: The development of palladium‐based catalysts for alkaline hydrogen evolution reaction (HER) is highly desired for renewable hydrogen energy systems, yet still challenging due to the strong palladium–hydrogen bond. Herein, the bottleneck is largely overcome by constructing a nitridation‐induced compressively strained‐interface N‐doped palladium/amorphous cobalt (II) interface (N‐Pd/A‐Co(II)), which dramatically boosts HER performance in alkaline condition. The optimized catalyst with the compressive strain of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The utilization of hydrogen energy is considered to be one of the important ways to reduce CO 2 emissions from traditional fossil fuel combustion. The water splitting is an efficient and clean approach to develop hydrogen energy, especially using the electricity generated by renewable energy. The recognized catalyst used to produce hydrogen efficiently through water splitting is the expensive and scarce Pt, which shows the best hydrogen evolution reaction (HER) performance for the most appropriate metal–H bond strength according to the typical Sabatier principle . However, this principle alone cannot explain the phenomenon that the HER activity of Pt under alkaline media is 2–3 orders of magnitude worse than that under acidic media. ,, It is suggested that the energy barrier of water dissociation under alkaline media is the key factor restricting the catalyst’s HER activity. , The recent studies show that ruthenium (Ru), which costs only about one-third of the price of Pt, shows superb HER activity under acidic or alkaline media. , Thanks to the water dissociation and *OH chemisorption capacity, many Ru-based catalysts show better HER performance than Pt under alkaline media. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The utilization of hydrogen energy is considered to be one of the important ways to reduce CO 2 emissions from traditional fossil fuel combustion. The water splitting is an efficient and clean approach to develop hydrogen energy, especially using the electricity generated by renewable energy. The recognized catalyst used to produce hydrogen efficiently through water splitting is the expensive and scarce Pt, which shows the best hydrogen evolution reaction (HER) performance for the most appropriate metal–H bond strength according to the typical Sabatier principle . However, this principle alone cannot explain the phenomenon that the HER activity of Pt under alkaline media is 2–3 orders of magnitude worse than that under acidic media. ,, It is suggested that the energy barrier of water dissociation under alkaline media is the key factor restricting the catalyst’s HER activity. , The recent studies show that ruthenium (Ru), which costs only about one-third of the price of Pt, shows superb HER activity under acidic or alkaline media. , Thanks to the water dissociation and *OH chemisorption capacity, many Ru-based catalysts show better HER performance than Pt under alkaline media. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The maximum performance for a specific quantity of Co present in the alloy was also found on other Co alloys [ 105 ]. Moreover, as reported by Li et al [ 48 ], the presence of amorphous Co has a beneficial effect on the HER performance because it accelerates the water dissociation. However, the quantity of the deposit must also be considered in relation to its morphology, that is related to the specific surface area.…”
Section: Resultsmentioning
confidence: 74%
“…Additionally, electrodes made of Pd and Co alloys have been shown to be much more efficient catalysts than pure Pd or Co [ 45 , 46 ] and they are similar to those of Pt. As reported in literature, this is due to the synergistic effect of amorphous Co sites and Pd sites [ 47 , 48 ] present in the alloy. Carbon paper (CP) was chosen as the support for the electrocatalyst because it is commonly used in PEMEL for the manufacture of the membrane electrode assembly (MEA).…”
Section: Introductionmentioning
confidence: 63%
“…Tuning surface strain has been proven as an efficient strategy for regulating the surface electronic properties and then the catalytic performance of metal catalysts. [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ] The strain effect on the atomic scale can lead to the change of lattice parameters, change the inherent atomic distance and modify the energy level of bonding electrons, thus greatly reducing the energy level barrier of HER.…”
Section: Strategies To Improve Her Electrocatalystsmentioning
confidence: 99%